Hubungan antara Status Gizi dan Prestasi Belajar Siswa - Rostikawaty, Intan Dwi; Hartati, Hartati; Triana, Noor Yunida (Prodi Keperawatan Purwokerto, 2025)
Background: Nutrition is one of the main determining factors in the quality of human resources. Good nutritional status will influence the growth and development process of children, which can improve intellectual abilities, which will have an impact on learning achievement at school. Objective: This research aims to determine the relationship between nutritional status and learning achievement of class VI students at SD Negeri Mandala 03, Cimanggu District, Cilacap Regency. Method: This research is a correlational and analytical design. The sampling technique was a total sampling of 34 respondents. Data analysis used the Spearman Rank test. Results: The findings show no relationship between nutritional status and the learning achievement of class VI students at SD Negeri Mandala 03, Cimanggu District, Cilacap Regency (p=0.712). Student learning achievement is not only influenced by nutritional status, but also they can be influenced by other factors, such as interest and motivation, environment, social media, ease of access to information, and genetic factors. Conclusion: Student learning achievement is not only influenced by nutritional status.